Analysis of still births in a tertiary care system and changed scenario over six year period - Mittal, Rita; Mittal, Shivika; Chandel, Anubala; Samyal, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In India, the maternal and infant mortality rates have been steadily decreasing in recent years, but there has been no corresponding decrease in the perinatal mortality. Hence, there is need to evaluate the factors leading to this unfortunate event. The objective of this study was to find out various factors (especially preventable) responsible for perinatal stillbirths. Methods: An analytical comparative study in a tertiary care hospital comparing fresh and macerated still births over a period of one year in 2011 and 2017 and responsible factors were analysed. Results: Amazingly, despite improvement in the antenatal services, more institutional deliveries, there is no change in the incidence of still birth rate. However, there was decrease in the rate of still births due to extreme prematurity and congenital malformations. There was no change in incidence of PIH/ Eclampsia, IUGR and placental causes but there was substantial increase in the incidence of GDM. Conclusions: Perinatal mortality can definitely be reduced by strengthening and improving quality of antenatal services, early identification of high risk pregnancies, timely referral and appropriate intervention.